Awareness of Research Methodology in Social Sciences - Moudgil, Anita (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Research is inevitable for the professionals for their career growth and for the cause of the society. Research must be done in systemic and righteous manner so that it augments the understanding of the real problem and facilitates the solution of the problems under consideration. It is important to have a deep understanding of research methodology for pursuing research in Social Sciences. A field survey on awareness about research methodology involve conducting research directly by interviewing researchers/teachers/professionals/ students from different academic backgrounds and sectors to assess their understanding and knowledge of key research methodologies. Nowadays, research has become popular in all the fields because it supports in decision-making. The present research paper is based on a field survey conducted in some areas of district Yamuna Nagar, Haryana. The research aims to measure the overall level of awareness about research methodology and its various steps and components and to identify specific areas where knowledge gaps exist regarding different research methods. Targeted Sampling: Participants from diverse academic disciplines, such as social sciences, humanities, Commerce have been selected using random sampling. The students of postgraduate classes from different streams and different colleges were included in the sample. The field survey report finds that there is general awareness about research methodology and plagiarism. There is lack of detailed and technical k knowledge about research techniques. The survey recommends that more and more research methodology workshops must be organised to develop research skills of the students. They should be taught about act of plagiarism and the types of plagiarism. The curriculum can be designed in a way which encourages students to undertake research.